Supplementation of Pandanus conoideus Oil in Cryopreservation Diluents for Maintaining the Semen Quality of Ongole Grade Bull - Nurcholis Nurcholis; A. Furqon; R. I. Arifiantini; S. M. Salamony (Faculty of Animal Science, Bogor Agricultural University, 2021)
Antioxidants such as tocopherol, ß-carotene, and polyunsaturated fatty acids (PUFA) from red fruit oil of Papua may be used to protect frozen semen. The study is aimed to test the effect of red fruit oil supplementation on motility, viability, and recovery rate of frozen sperm of Ongole-grade bulls. Semen was collected twice a month from eight 4-5-year-old male Ongole grade using an artificial vagina, followed by macro- and microscopical evaluations. Collected semen was divided into four tubes and diluted with tris egg yolk diluents (TEY) as a control, TEY supplemented with 0.5% red fruit oil (RFO) (TEY RFO0.5), TEY supplemented with 1% RFO (TEY RFO1.0), and TEY supplemented with 1.5% RFO (TEY RFO1.5). The diluted semen was then packed into the straw and equilibrated for 2, 4, and 6 h prior to frozen on liquid nitrogen vapor for 10 minutes. The observed variables in this study were sperm motility, sperm viability, and morphology after equilibration, after thawing, and recovery rate. The experimental design is a completely randomized factorial design. The data were analyzed using ANOVA and were further tested using Duncan multiple range test. The results showed that the sperm motility of fresh semen was 81.10±1.42%. The percentage of sperm motility in TEY RFO1.5 treatment at 6 h equilibration was 60.00±1.06%, significantly higher compared to TEY RFO1.0 and TEY RFO0.5. The percentage of post-thawing sperm motility in TEY RFO1.5 treatment was 62.40±1.09%. The best post-thawing sperm viability in TEY RFO1.5 was 80.70±1.20%, significantly increase from the treatment of TEY RFO1.0 and TEY RFO0.5. The recovery rate (RR) for TEY RFO1.5 treatment had the best percentage at 76.94%. In conclusion, RFO supplementation in semen diluents for 2 h of equilibration resulted in the best motility and viability at 0 h of post thawing observation.